PERAN MANAJEMEN KELAS DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS IV DI MADRASAH IBTIDAIYAH MATHA’UL ANWAR PILAR SIBANTENG - Dede Hidayatulloh; Agus Tamami (Institut Ummul Quro Al-Islami Bogor, 2024)
Student success in the learning process depends heavily on teacher strategies, efforts to increase student activity, and how to create a dynamic learning environment in the classroom. Effective classroom management can also contribute to achieving the desired learning objectives. It involves the role of various elements involved in the learning process. The purpose of this study is to identify the role of classroom management in increasing the learning activity of grade IV students in Madrasah Ibtidaiyah Mathla'ul Anwar pilar sibanteng. This research applies qualitative research methods. The research was conducted at the Ibtidaiyah Mathla'ul Anwar Pilar sibanteng madrasah during the period, January 2023 to July 2023. Participants in this study consisted of 4 grade IV teachers, 2 homeroom teachers IV, 1 grade IV student, and 1 grade IV student. Data collection methods used include interviews, observation, and documentation, data presentation, as well as conclusion making and verification. The results showed that classroom management carried out by teachers includes several aspects, such as learning planning (RPP, Prosem, and Prota), providing facilities for teaching and learning activities, forming class organizational structures, scheduling pickets, and implementing monthly evaluations. The learning activity of grade IV students at MIMA Pilar is caused by several factors, such as the environment, family background, and teacher teaching methods. Greatly affects the learning effectiveness of IV students at MIMA Sibanteng pillar